Do the Hands that Feed Us Hold Us Back?: Implications of Assisted Eating - G. Denise Lance (Disability Studies Quarterly, 2007)
The purpose of this article was to investigate the social implications of assisted eating. Email interviews were conducted with six people with disabilities who need eating assistance. The author also explored her own experiences as a person with cerebral palsy who must be fed. All the interviewees reported avoiding events which involved food at one time or another on the basis of having to be fed. Although many were uncomfortable being fed in public at the onset of disabilities, they used the strategies of: eating before or after an event, selecting foods they could feed themselves, or bringing an assistant. The interviews and author's experiences revealed several possible relationships between assisted eating and the building of social capital.
Keywords: Disabilities; social capital; feeding; assisted eating